Simulation of genetic algorithm scheduling on extendsim based on COM t;echnology - Zhang, Shi Shan; Peng, Hui; Liu, Chang; Yao, Li Li (2012 International Conference on Modelling, Identification and Control, 2012)
In the study of production scheduling problem, sometimes it is necessary to verify the result of the research by the simulation. ExtendSim, powerful system simulation software, can access code created in varieties of programing languages using its built-in APIs. However there is almost no relevant research literature in data interaction between ExtendSim and C#. This Paper presents a method that uses COM technology to complete it. At first, A COM interface is established on C#.Net platform. Then a simulation environment is founded in the ExtendSim. By calling the interface, ExtendSim achieves data interaction with C#.Net. What's more, this paper verifies the feasibility and effectiveness of the technology through an instance that genetic algorithm solves production scheduling problem, which adds a new solution for the simulation of the production scheduling problem.